2016
DOI: 10.1007/s00246-016-1527-z
|View full text |Cite
|
Sign up to set email alerts
|

Intact Imaging of Human Heart Structure Using X-ray Phase-Contrast Tomography

Abstract: Structural examination of human heart specimens at the microscopic level is a prerequisite for understanding congenital heart diseases. It is desirable not to destroy or alter the properties of such specimens because of their scarcity. However, many of the currently available imaging techniques either destroy the specimen through sectioning or alter the chemical and mechanical properties of the specimen through staining and contrast agent injection. As a result, subsequent studies may not be possible. X-ray ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 13 publications
0
32
0
Order By: Relevance
“…Finally, we have shown 15 that phase-contrast microCT (which does not rely on exogenous contrast agents) can quantify differences in the sub-micron structure of rat carotid arteries as a consequence of intra-luminal pressure and, using a high-flux synchrotron X-ray source, collagen orientation within the annulus fibrosus of native (unfixed and unstained) intervertebral disc 23. This technique is becoming more popular in cardiovascular research 20,24,25, probably because of its potential clinical relevance 26. However, despite the potential of high-resolution microCT imaging to visualise the internal micro-structure of blood vessel walls 15, it has not been applied to characterise 3D remodelling as a consequence of MFS-associated aneurysms and/or ageing.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we have shown 15 that phase-contrast microCT (which does not rely on exogenous contrast agents) can quantify differences in the sub-micron structure of rat carotid arteries as a consequence of intra-luminal pressure and, using a high-flux synchrotron X-ray source, collagen orientation within the annulus fibrosus of native (unfixed and unstained) intervertebral disc 23. This technique is becoming more popular in cardiovascular research 20,24,25, probably because of its potential clinical relevance 26. However, despite the potential of high-resolution microCT imaging to visualise the internal micro-structure of blood vessel walls 15, it has not been applied to characterise 3D remodelling as a consequence of MFS-associated aneurysms and/or ageing.…”
Section: Introductionmentioning
confidence: 99%
“…The system used, and its processing values, have been described in detail elsewhere. 8,9 Briefly, the system was located 200 m from the synchrotron X-ray source. The X-ray energy was tuned to 25 keV by passing through a Si (111) double-crystal monochromator.…”
Section: Methodsmentioning
confidence: 99%
“…6,7 As yet, however, at least to the best of our knowledge, no measurements have been provided to guide the placement of sutures on the right or left sides of the septal structures during surgical closure of the interatrial component of the septal defect so as to avoid iatrogenic heart block. 8,9 The precise dimensions of the ventricular components of the conduction axis are similarly as yet unknown. We have now shown that, when using phase-contrast computed tomography, it is possible to demonstrate the precise location of the conduction axis relative to its surroundings without destroying or altering the properties of autopsied human heart specimens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the advent of phase-contrast micro-CT and improvements in data acquisition and reconstruction, it has now become possible to characterize the entire heart with voxel sizes in the range of a few micrometers using synchrotron radiation [7][8][9][10][11][12], or even laboratory x-ray sources [13]. These results indicate that the heart is a complex 3d mesh of aggregated cardiomyocytes with a supporting fibrous matrix [1,4].…”
Section: Introductionmentioning
confidence: 99%